Foreign-language comprehension, composition skills and strategy use - Siladi Vasyl; Szilágyi László; Сіладі Василь (CPN Publishing Group, 2019)
Abstract. The comprehension of foreign language text and the writing of written text have been the focus of domestic and international research several times. This paper combines the two areas with area-specific strategy use. Reading comprehension and written writing assignments play a dominant role in foreign language teaching.
https://sci-conf.com.ua/wp-content/uploads/2019/11/perspectives-of-world-science-and-education_27-29.11.19.pdf
Keywords: language learning strategies; language acquisiton; foreign language literacy